Formulasi Model Resiliensi Anak Pasca Perceraian Berbasis Surah al-Ṭalaq dan al-Nisā’ di Kelurahan Sijambi - Salsabila Nayla; Junaidi Junaidi; Wahyu Wiji Utomo (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2026)
The increasing divorce rate in various regions of Indonesia has created serious problems for children’s psychological resilience. At the same time, conventional approaches to family psychology tend to be partial and have not been integrated with the normative values ​​of the Qur’an. The focus of this study is directed at identifying resilience values ​​in Surah al-Ṭalaq and al-Nisā’, mapping the empirical conditions of children after divorce in Sijambi Village, and formulating a contextual, Qur’an-based resilience model. An integrative qualitative approach was used through a thematic interpretation study (mawḍūʻī) and a field study using data collection techniques such as in-depth interviews, participatory observation, and documentation, which were then analyzed using thematic and interactive models. The main findings indicate the existence of resilience values in the Qur’an, including dimensions of spiritual strengthening, emotional regulation, social responsibility, and child welfare guarantees, which function in both preventive and curative ways. Empirical conditions show variations in children’s resilience levels, influenced by the quality of family relationships, social support, and economic stability after divorce. The gap between normative values ​​and social practices is still evident in the weak internalization of religious values ​​in parenting. The formulation of an integrative, contextual, and applicable Qur’an-based resilience model has implications for strengthening family, educational, and community interventions in sustainably building children’s resilience.